2018
DOI: 10.1161/circinterventions.117.005727
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Prognosis Markers of Patients With Liver Disease Undergoing Transcatheter Aortic Valve Replacement

Abstract: These findings suggested that TAVR is a feasible treatment for severe aortic stenosis in patients with early-stage liver disease or as bridge therapy before a curative treatment of the hepatic condition. Patients with Child-Pugh class B-C, especially in combination with renal impairment, had a very low survival rate, and TAVR should be carefully considered to avoid a futile treatment. These results may contribute to improve the clinical decision-making process and management in patients with liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 42 publications
1
36
3
Order By: Relevance
“…(19,20) In the largest cohort to date, Tirado-Conte et al reported 1-year mortality rate of 37% after TAVR among 114 patients with chronic liver disease, 83 of whom had cirrhosis. (21) This rate is comparable to a 1-year mortality rate of 29% in our TAVR cohort. Taken together, long-term survival in our study is comparable to previous studies, with in-hospital mortality being lower in our group.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…(19,20) In the largest cohort to date, Tirado-Conte et al reported 1-year mortality rate of 37% after TAVR among 114 patients with chronic liver disease, 83 of whom had cirrhosis. (21) This rate is comparable to a 1-year mortality rate of 29% in our TAVR cohort. Taken together, long-term survival in our study is comparable to previous studies, with in-hospital mortality being lower in our group.…”
Section: Discussionsupporting
confidence: 76%
“…Other studies included 8 to 83 patients with cirrhosis undergoing TAVR, with the longest median follow-up being 13 months. (18)(19)(20)(21)(22) Greason et al reported no deaths at 7 months in a smaller data set from our center. (18) Wendt et al reported a 30-day mortality rate of 9.1%, (18) and Shah et al and Pascual et al reported median survival of 2.7 years.…”
Section: Discussionmentioning
confidence: 52%
“…18,19 A study by Tirado-Conte comparing TAVR in patients with and without cirrhosis showed no difference in in-hospital and 30-day mortality, stroke, major vascular complications, bleeding complications, and new pacemaker implantation. 23 However, patients with cirrhosis had a higher rate of acute kidney injury. 23 In an analysis of the 2-year outcomes of the PARTNER (Placement of AoRTic TraNscathetER Valve) trial, the presence of liver disease was predictive of mortality in patients undergoing SAVR but not TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, patients with cirrhosis had a higher rate of acute kidney injury. 23 In an analysis of the 2-year outcomes of the PARTNER (Placement of AoRTic TraNscathetER Valve) trial, the presence of liver disease was predictive of mortality in patients undergoing SAVR but not TAVR. 24 Patients with cirrhosis have pathophysiologic states that predispose them to surgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Included patients were classified into two groups: (a) without severe comorbidities and (b) with severe comorbidities and potential lack of mortality or quality of life benefit. As we previously described 20 and on the basis of results from previous studies, 21‐25 severe comorbidities were defined as the presence of any of the following criteria: severe lung disease (chronic lung disease patients who were either poorly mobile or oxygen‐dependent), severe liver disease (Model for End‐Stage Liver Disease >12), end‐stage renal disease (stage V) on dialysis treatment, severe malignancy (i.e., metastatic malignancy with life expectancy >1 year), severe dementia, severe dilated cardiomyopathy (ejection fraction <30%) and frailty. As previously described, 25 frailty status was defined as the presence of any three of the five components: a body mass index (BMI) < 20 kg/m 2 ; serum albumin <3.5 g/dl; Katz index of independence in activities of daily living score ≤ 4/6; low grip strength; and slow 15‐foot walk time.…”
Section: Methodsmentioning
confidence: 99%